Creative motion graphic titling for film, video, and the web. - Braha, Yael, ....-; Byrne, Bill, ....- (Amsterdam : Elsevier, 2011)
Captivate your audience and enhance your storytelling with this tutorial based 4-color cookbook, featuring dozens of solutions to your titling needs. Each chapter includes case studies and interviews with the pros, lending cutting insight and lessons learned that will have you creating inspired title sequences in no time. The book features genre-based tutorial sections, with step by step instructions for creating effective horror, comedy, drama, and suspense titling sequences. Tutorials for creating some of the most popular title sequences in blockbuster movies are included (Se7en, The Sopranos, 24, The Matrix). Other tutorials teach you how to effectively use sound and VFX in your titles, and also included is instruction on editing your title sequence. These techniques, as well as chapters on the essentials of typography allow you to apply these lessons to your title sequence regardless of whether it's for TV, the web, or digital signage. Also included is a DVD with sample clips, as well as project files that allow you to refine the techniques you learned in the book. As an added bonus we've included 3 titling chapters from other Focal books, with specific instructions on titling within certain software applications.